Moscas ectoparasitas (Diptera, Streblidae) de morcegos filostomídeos (Mammalia, Chiroptera) na Estação Ecológica dos Caetetus, São Paulo, Brasil - Graciolli, Gustavo; Passos, Fernando C.; Pedro, Wagner André [UNESP]; Lim, Burton K. (Sociedade Brasileira de Zoologia, 2006)
Levantamento das espécies de moscas ectoparasitas de morcego da família Streblidae sobre morcegos da família Phyllostomidae foi realizado na Estação Ecológica de Caetetus, São Paulo. Foram capturados 400 indivíduos de 15 espécies de morcegos filostomídeos, mas somente seis espécies abrigavam 93 indivíduos de nove espécies de Streblidae. A prevalência e intensidade média são apresentadas para cada espécie de Streblidae. Strebla chrotopteri Wenzel, 1976 é registrada pela primeira vez no Estado de São Paulo.

A survey of species of streblid bat flies on phyllstomid bats was carried out at Caetetus Ecological Station, São Paulo. We captured 400 individous of 15 species of phyllostomid, but just six species harboured 93 individous of nine species of Streblidae. The prevalence and mean intensity, are given for each species of bat fly. Strebla chrotopteri Wenzel, 1976 is reported for the first times in state of São Paulo.
Bat flies (Diptera, Streblidae) on phyllostomid bats (Mammalia, Chiroptera) from Caetetus Ecological Station, São Paulo, Brazil
Keywords: Ectoparasito; intensidade média; Phyllostomidae; prevalência; Ectoparasite; mean intensity; Phyllostomidae; prevalence